Cost-effectiveness of a new system in ruling out negative urine cultures on the day of administration - İLKİ, ZEYNEP ARZU (SPRINGER, 2017)
Urine samples account for a significant part of the workload in clinical microbiology laboratories. However, the culture process is time-consuming and a large proportion is reported as negative. To reduce unnecessary culture procedures and speed up the reporting of negative results, a reliable screening method is needed. For this purpose, urine samples submitted to our clinical microbiology laboratory were simultaneously screened by a flow cytometry method (Sysmex UF-1000i, Japan). During screening, the evaluation of various combinations of leucocytes and bacteria cut-offs demonstrated that cut-offs of 30 and 50/mu L, respectively, were the best threshold values to reach a 100% negative predictive value (NPV) with a culture reduction rate of 44.8% in adults and 61.9% in children between the ages of 6 and 17 years. With the culture reduction rates mentioned above, the screening method has provided at least 24% savings in expenditures of the routine clinical microbiology laboratory. Since we did not reach such an NPV with any combinations of screening parameters in children younger than 5 years of age, we recommend cultivation of all urine samples in those patients without a screening step. In conclusion, Sysmex UF-1000i as a screening method was capable of improving the efficiency of the routine microbiology laboratory by providing negative results in a few minutes in children greater than 6 years of age and in adults.
Keywords: FLOW-CYTOMETRY; SIGNIFICANT BACTERIURIA; TRACT-INFECTIONS; SPECIMENS; DEVICE